SINDROM PASCA COVID-19 - Aprilia Sari; Yeni Mahwati (stikes dharma husada bandung, 2023)
Background: The phenomenon of post-COVID-19 syndrome is still largely unreported in Indonesia. Post-COVID-19 syndrome itself has not been widely studied, resulting in a lack of promotive and preventive measures for patients who experience post-COVID-19 syndrome. Objective: To determine the syndrome experienced by COVID-19 survivors and the factors that influence the occurrence of post-COVID-19 syndrome. Methods: Literature search using Google Scholar and Pubmed databases with a range of years 2019-2023. With keywords